Clinical and biochemical efficacy zoledronic acid and denosumab combination: focus serum inflammatory factor level (serum ifcs), bone gla protein (bgp), and bone turnover markers b-collagen degradation product (b-ctx), and procollagen type 1 n-terminal propeptide (p1np) - Kong Lingyan; Ma Jun (Journal of Medical Biochemistry)
Background: Postmenopausal osteoporosis (PMOP) is a prevalent metabolic bone disorder characterized by decreased bone mineral density (BMD) and skeletal fragility, leading to increased susceptibility to fractures. The therapeutic efficacy of zoledronic acid and denosumab, two widely used agents in the treatment of osteoporosis, was investigated in this study. The primary objective was to evaluate the clinical effects of zoledronic acid and denosumab on serum inflammatory cytokine (IFC) levels and BMD in PMOP patients. Methods: A prospective, non-blinded, randomized controlled trial was conducted at our hospital from March 2021 to March 2024. Eighty PMOP patients were recruited and randomly assigned to either a control group (CG, n=40) or a treatment group (TG, n=40). The CG received zoledronic acid plus traditional treatment, while the TG received zoledronic acid plus denosumab plus traditional treatment. Clinical symptom improvement and changes in BMD were assessed and compared between the two groups. Serum IFC levels, including bone Gla protein (BGP) and bone turnover markers b-collagen degradation product (b-CTX) and procollagen type 1 N-terminal propeptide (P1NP), were measured. Results: Compared to the CG, patients in the TG demonstrated significantly increased BMD (P<0.05) and decreased levels of serum IFCs, BGP, and bone turnover markers (P<0.05). Additionally, the incidence of adverse reactions was significantly lower (P<0.05) in the TG, and the total effective rate of clinical treatment was significantly higher (P<0.05). Conclusions: The combination of zoledronic acid and denosumab exhibited improved clinical efficacy in PMOP patients, as evidenced by enhanced BMD and reduced serum IFC levels. These findings suggest that this combined treatment regimen may promote the treatment of osteoporosis by suppressing inflammatory responses, thereby providing a novel therapeutic approach for the management of PMOP.